Comparative Study Of Conventional And Sbci Cardboard Solar Ovens - Nandwani, Shyam S. (1992)
Two folding and light solar ovens designed and constructed by Solar Box Cookers International (SBCI), Sacramento, U.S.A., have been studied experimentally. Furthermore, their performance is com pared with standard two glass solar ovens designed by one of us (S.S.N.), in the climate of Costa Rica. According to our measurements, made with and without load, taken during 30 different days, both cardboard ovens are 15-25% less efficient than the conventional oven and, secondly, the improved SBCI oven is slightly better than the previous SBCI oven.